Clinical manifestations and outcome of Mpox infection in Qatar: An observational study during the 2022 outbreak - Ahmed Zaqout; Joanne Daghfal; Waqar Munir; Alaaeldin Abdelmajid; Soha S. Albayat; Mohammed Abukhattab; Muna A. Al-Maslamani (Journal of Infection and Public Health, 2023)
Mpox emerged in May 2022 as a global outbreak, mostly in hitherto non-endemic countries. To describe the epidemiological and clinical characteristics of mpox in Qatar, data were retrospectively retrieved for all laboratory-confirmed mpox cases diagnosed in Qatar between May and November 2022. Twelve cases were identified; of which 10 were males, and the median age was 33.5 years (IQR 24.5–37.5). Recent sexual exposure was reported in 9 patients, 6 of which were outside Qatar. Seven individuals reported exclusive heterosexual contact. Pleomorphic skin lesions were present in all cases, with anogenital involvement in 11. Fever (7/12) and lymphadenopathy (4/12) were relatively common. All cases were HIV-negative. The majority of cases had an uncomplicated and self-limiting clinical illness. In conclusion, the majority of early mpox infections in Qatar were purportedly acquired through heterosexual contact, primarily among middle-aged men. The clinical course was mostly uneventful. In the absence of active case finding and the mild and self-limiting nature of the clinical illness, undetected community transmission cannot be ruled out.